TINDAK TUTUR DIREKTIF DAN EKPRESIF DALAM ACARA DEBAT YANG KEDUA CALON WAKIL PRESIDEN REPUBLIK INDONESIA - Mesy Agustin Mesy; Juaidah Agustina; Masnunah (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to determine the directive and expressive speech acts used by the Vice Presidential Candidates in the second Debate event for the 2023 Vice Presidential Candidates of the Republic of Indonesia Muhaimin Iskandar, Gibran rakabumung Raka, and Mahfud MD. This research method uses the Qualitative Descriptive Method. The results of this research show that: (1) Directive Speech Acts in the 2023 Indonesian Vice Presidential Candidate Muhaimin Iskandar, Gibran Rakabumung Raka, and Mahfud MD Debate Event contained the words: Request, Order, Oppose, and Advise; (2) Speech Acts Expressive with words; Greetings, Apologizing, Criticizing, Flattering, Praising, Thanking.